(untitled) (Jurnal Teknologi (Sciences & Engineering), 2021)
This study is motivated by the need to mitigate damages caused by mudflow disaster, which is occurring frequently due to intensive forest clearing and uncontrolled land use at highland. Numerical modelling of mudflow is challenging as the propagation speed and rheological behavior of the flow relies on the accuracy of the numerical scheme and choice of rheological model. In this study, a two-dimensional depth-averaged model was developed to simulate a simplified mudflow event. In order to capture shock in mudflow, the finite volume method (FVM) with third order accurate Monotonic Upstream-centered Scheme of Conservation Laws (MUSCL) scheme was adopted in the numerical model and the model was verified against a benchmark partial dam-break problem. By assuming that the mudflow has high amount of fine mud suspension. the rheological model was represented by a simplified Herschel-Bulkley model. Numerical results showed that the Herschel-Bulkley model could reproduce the viscoplastic behavior of mudflow well, especially in the estimation of final longitudinal flow spreading (2% difference compared to experimental value) and depth of peak wave (8.8% maximum difference). The robustness and stability of the model was demonstrated by simulating a simplified mudflow event with obstacles.